Democracy, difference, and social justice - Mahajan, Gurpreet (Delhi : New York : Oxford University Press, 1998)
This text examines how differences have been understood and accommodated within democratic theory. It presents strategies of social justice that have evolved to take care of discrimination resulting from social and cultural differences, and contextualizes these concerns in relation to India.
Includes bibliographical references and index.
Keywords: Democracy; Social justice